Effect of arm cranking on oxygenation of vastus lateralis and lateral gastrocnemius muscles during leg cycling - Ogata, H.; Yano, T. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The purpose of this study was to compare the changes in oxygenation in exercising vastus lateralis muscle (VL) and lateral gastrocnemius muscle (LG) when arm cranking is added to on-going leg cycling. Methods: Change in oxygenation (difference between concentrations of oxygenated hemoglobin and deoxygenated hemoglobin, HbD) was determined using near-infrared spectrometry. Before the combined exercise, each subject (n=8) rested for 5 min and then performed 10-min constant-work-rate leg cycling. The intensities of leg cycling were 20% and 40% of peak oxygen uptake (V.O2peak) during incremental leg cycling (LC20 and LC40). Arm cranking at an intensity of 60% of V.O2peak recorded during incremental arm cranking (AC60) was added to the on-going leg cycling (both AC60LC20 and AC60LC40 in two separate sessions) for 6 min. Results: During AC60LC20, HbD in both the VL and LG showed significant decreases compared to the control value (1 min before combined exercise: LC20). During AC60LC40, a significant decrease in HbD compared to the control value (1 min before combined exercise: LC40) was observed only in the LG. In the VL, the integrated electromyogram (iEMG) during AC60LC40 was significantly larger than that during AC60LC20, whereas in the LG, no significant difference was found between the iEMG during AC60LC40 and that during AC60LC20. These results suggest that the decrease in HbD in the exercising leg muscles is related to the level of its muscle activity after the addition of arm cranking. Conclusion: The results suggest that HbD shows different changes in exercising leg muscles due to the difference in its activity level when arm cranking is added to on-going leg cycling.